2022
DOI: 10.1155/2022/4782361
|View full text |Cite|
|
Sign up to set email alerts
|

Long Noncoding RNA SBF2-AS1 Promotes Abdominal Aortic Aneurysm Formation through the miRNA-520f-3p/SMARCD1 Axis

Abstract: Abdominal aortic aneurysm (AAA) is a chronic vascular inflammatory disease. The regulatory mechanisms during AAA formation remain unclear. Bone marrow stem cells (BMSCs) are pluripotent cells capable of regulating the progression of various diseases by delivering exosomes and exosomal lncRNAs. In this study, we investigated its function in AAA by isolating BMSC exosome-derived lncRNA SBF2-AS1. The results showed that BF2-AS1 could be transferred to vascular smooth muscle cells (VSMCs) and human aortic VSMCs (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The progression of AAA is strictly related to the up-regulation of apoptotic markers, i.e., Cas3 [49]. Deregulated expressions of miRNA level, as miR-520f-3p, miR-155-5p and miR-1-3p, were proposed as transcriptional biomarkers of AAA disease, among others, leading to apoptosis [50][51][52]. A specific type of cell death is ferroptosis.…”
Section: Abdominal Aorta Aneurysm-cellular Physiology and Pathophysio...mentioning
confidence: 99%
“…The progression of AAA is strictly related to the up-regulation of apoptotic markers, i.e., Cas3 [49]. Deregulated expressions of miRNA level, as miR-520f-3p, miR-155-5p and miR-1-3p, were proposed as transcriptional biomarkers of AAA disease, among others, leading to apoptosis [50][51][52]. A specific type of cell death is ferroptosis.…”
Section: Abdominal Aorta Aneurysm-cellular Physiology and Pathophysio...mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%